2016
DOI: 10.1093/hmg/ddw204
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of TMEM97 increases NPC1 protein levels and restores cholesterol trafficking in Niemann-pick type C1 disease cells

Abstract: Niemann-Pick type C disease (NP-C) is a progressive lysosomal lipid storage disease caused by mutations in the NPC1 and NPC2 genes. NPC1 is essential for transporting cholesterol and other lipids out of lysosomes, but little is known about the mechanisms that control its cellular abundance and localization. Here we show that a reduction of TMEM97, a cholesterol-responsive NPC1-binding protein, increases NPC1 levels in cells through a post-transcriptional mechanism. Reducing TMEM97 through RNA-interference redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
100
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 47 publications
3
100
0
Order By: Relevance
“…A compensatory overexpression of NPC1-I1061T, in transgenic NPC1 mouse and cat models, was able to provide a partial correction of the disease phenotype [16]. In agreement with these data, it has also been shown that pharmacological treatments that lead to upregulation of NPC1 variant expression, including ryanodine receptor antagonists [17], treatment with oxysterols that bind to and stabilize NPC1 [18], reduced expression of TMEM97 [19], and HDAC inhibitors [20], partially abrogate the NPC1-I1061T phenotype in heterologous cell and patient fibroblast models. These findings highlight that modulation of the local folding and signaling environment can facilitate disease correction [21][22][23][24].…”
Section: Introductionsupporting
confidence: 59%
“…A compensatory overexpression of NPC1-I1061T, in transgenic NPC1 mouse and cat models, was able to provide a partial correction of the disease phenotype [16]. In agreement with these data, it has also been shown that pharmacological treatments that lead to upregulation of NPC1 variant expression, including ryanodine receptor antagonists [17], treatment with oxysterols that bind to and stabilize NPC1 [18], reduced expression of TMEM97 [19], and HDAC inhibitors [20], partially abrogate the NPC1-I1061T phenotype in heterologous cell and patient fibroblast models. These findings highlight that modulation of the local folding and signaling environment can facilitate disease correction [21][22][23][24].…”
Section: Introductionsupporting
confidence: 59%
“…11,12 σ 2R/TMEM97 has long been associated with cancer, 13,14 and it is increasingly being implicated in cellular processes relevant to a variety of CNS disorders, 10,15 including Alzheimer's disease (AD), 8,16–18 schizophrenia, 10 anxiety, pain, 19 and Niemann-Pick disease. 12 …”
Section: Introductionmentioning
confidence: 99%
“…After decades of studies, cholesterol biology remains inadequately understood, in particular, the regulations involving lysosomes, which distribute cholesterol to other organelles 1 . Recently, TMEM97 was reported as a novel player in cholesterol transport 2,3 . An ER resident protein, TMEM97 can translocate to the lysosomal membrane where it appears to attenuate the activity of NPC1 (Niemann-Pick disease, type C) 3 , the transporter that "pumps" cholesterol out of the lysosome.…”
Section: Introductionmentioning
confidence: 99%